Parameters influence on acceleration and deceleration capacity based on trans-abdominal ECG in early fetal growth restriction at different gestational age epochs. (May 2015) - Stampalija, Tamara; Casati, Daniela; Montico, Marcella; Sassi, Roberto; Rivolta, Massimo W.; Maggi, Valeria; Bauer, Axel; Ferrazzi, Enrico
Abstract: Objective: Intrauterine growth restriction (IUGR) is characterized by chronic nutrient deprivation and hypoxemia that alters the autonomous nervous system regulation of fetal heart rate variability (fHRV). Phase-rectified signal averaging (PRSA) is a new algorithm capable to identify periodic and quasi-periodic patterns of HR, and which is used to quantify the average acceleration and deceleration capacity (AC/DC) of the heart. The computation of AC/DC depends on the parameters T and s, which we set so that s  =  T . T and s determine the periodicities that can be detected (the larger T the smaller the frequency of oscillations for which the method is most sensitive). The aim of the study was to evaluate the influence of the parameter T on PRSA computation, based on trans-abdominally acquired fetal ECG (ta-fECG), in early IUGR (<34 weeks of gestation) at two different gestational age epochs. Study design: AC/DC were calculated for different T values (1 ÷ 45) on fetal RR intervals derived from ta-fECG in 22 IUGR and in 37 appropriate for gestational age (AGA) fetuses matched for gestational age, in two gestational age epochs: very preterm group (≥26 ÷ <30 weeks), and preterm group (≥30 ÷ <34 weeks), respectively. Results: AC/DC were significantly lower in IUGR than in AGA fetuses for all T  ≥ 5 values ( p  < 0.05). The best area under the receiver operating characteristic curve (AUC) in identifying IUGR at time of recording was observed for T9 [AUC AC-T9 0.87, 95% confidence interval (CI) 0.77–0.96; and AUC DC-T9 0.89, 95% CI 0.81–0.98), and in range of T 7 ÷ 15. In the same T interval, AC/DC were significantly lower in very preterm than in preterm IUGR group ( p  < 0.05), while there were no differences in AGA fetuses at two gestational age epochs ( p  > 0.05), respectively. The AUCs of AC-T9 and DC-T9 significantly outperformed that obtained by short-term variation (AUC 0.77, 95% CI 0.65–0.90; p  = 0.009 and p  = 0.003, respectively). Conclusions: Our study shows that within the range of T parameter 1 ÷ 45, T  = 9 proved to be the best value to discriminate the AC and DC of the fetal heart rate of IUGR from AGA fetuses prior to 34 weeks of gestation. These significant differences are emphasized in very preterm gestational age epochs.